Local dynamic stability of the trunk after prolonged seating with axial load. (September 2022) - Le, Peter; Weisenbach, Charles A.
Abstract: Fatigue from prolonged seating with an axial load on the trunk may impair neuromuscular control and spine stability which may elevate risk of low back pain (LBP) for dynamic tasks following seating. The objective of this study was to assess local dynamic trunk stability using the maximum Lyapunov exponent (λMAX ) with corresponding coactivation patterns to understand possible effects from prolonged seating. An increase in λMAX would indicate decreased stability. Twenty participants (10 male, 10 female) performed a controlled, cyclic sagittal flexion task at 40 cycles per minute before and after three hours of seating in a simulated helicopter-seating environment with a weighted vest. A statistically significant decrease was seen in λMAX (bits/s) (Pre-Test = 0.654 ± 0.172; Post-Test = 0.829 ± 0.268, p  = 0.002), trunk cumulative coactivation index (unitless/s) (Pre-Test = 1.71 ± 0.97; Post-Test = 1.59 ± 0.96, p  = 0.0095), and abdominal activation (normalized) (Pre-Test = 0.46 ± 0.17, Post-Test = 0.41 ± 0.18, p  = 0.0146) post-seating exposure. Trunk extension was reduced (∼4°, p  = 0.0004) during the post-seating cyclic test with slight corresponding increases in flexion. This study provides evidence of potential effects of fatigue from prolonged seating to neuromuscular control, which may have implications for occupations requiring highly dynamic tasks after prolonged seated postures. Future studies would repeat the tests with dynamic environments (i.e., vibration), test the cyclic flexion protocols with different seating interventions, and continue to test the approach to develop a tool to assess back impairment or intervention effectiveness.